Current Status of Genus Bryum Hedw. in Eastern Himalaya, India - Pooja Bansal (Taiwania, 2013)
A critical study on the genus Bryum Hedw., an acrocarpous moss of family Bryaceae, revealed the occurrence of 21 species from seven state of eastern Himalaya: Arunachal Pradesh, Assam, Manipur, Meghalaya, Nagaland, Sikkim and West Bengal. Among these twenty one species, B. argenteum var. griffithii (Muell. Hal.) Gangulee, B. billardieri Schwaegr., B. pallescens Schleich. ex Schwaegr., B. pseudotriquetrum (Hedw.) P. Gaertn., B. Meyer & Scherb., B. pseudotriquetrum var. subrotundum (Brid.) Gangulee and B. reflexifolium (Ochi) Ochi are new additions to Meghalaya; B. billardieri Schwaegr. to Manipur while B. apiculatum Schwaegr., B. caespiticium Hedw. and B. pseudotriquetrum var. subrotundum (Brid.) Gangulee are new for West Bengal. Identification key to all the known species of the genus occurring in eastern Himalaya, alongwith the notes on their ecology and distribution have been provided.